Upaya Institusi Sosial dalam Menanggulangi Keberadaan Orang Dengan Gangguan Jiwa (ODGJ) Terlantar (Studi terhadap Institusi Sosial Fornal Dinas Sosial Kota Serang) - Anten Fhabella; Subhan Widiansyah; Stevany Afrizal (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2024)
This article aims to describe the efforts of the Serang City Social Service in dealing with the presence of neglected people with mental disorders (ODGJ). The existence of abandoned people with mental disorders (ODGJ) in Serang City is caused by families not being able to care for and treat them at home, families let them wander outside the house which ultimately causes people with mental disorders (ODGJ) to become abandoned, and families lock up their family members who Having a mental disorder also makes his condition worse. There is a need for an institution to handle the existence of abandoned people with mental disorders (ODGJ), namely the Serang City Social Service which has the authority to deal with the existence of abandoned people with mental disorders (ODGJ) through the ATENSI program. Giddens in structuration theory, there are agents and structures that give rise to social practices in the form of daily routines for people with mental disorders (ODGJ) who are abandoned while in halfway houses. Meanwhile, according to Scott, there are pillars on which an institution is built, namely the regulative, normative and cultural-cognitive pillars. In this research, it was found that these three pillars went hand in hand, resulting in the establishment of an institution for the Serang City Social Service that could create stability in life in society.